Bidentate ligand-catalyzed enantioselective addition of RZnX to benzaldehyde - Jagtap, Ravindra S.; Joshi, Navalkishore N. (Tetrahedron Letters, 2011)
{Enantioselective addition of RZnX (R = alkyl
Keywords: 1; 2-Addition; Asymmetric synthesis; Chelating ligands; Organozinc

Base-catalyzed mukaiyama-type aldol additions, a continued quest for stereoselectivity - Sutar, Revannath L.; Joshi, Navalkishore N. (Tetrahedron-Asymmetry, 2013)
Base-catalyzed reactions of silyl enolates with carbonyl compounds are an attractive variant of conventional directed aldol reactions. Over the past two decades, the reaction has gained prominence due to its inherent advantage for stereoselective manipulations. The present review provides a brief account of developments in this area. Various approaches are grouped together in order to provide the salient features of each conceptual development. It appears that the methods which generate nascent chiral enolates or cationic siliconium species have the biggest influence on the stereoselectivity. (C) 2013 Elsevier Ltd. All rights reserved.